2018
DOI: 10.26444/aaem/99641
|View full text |Cite
|
Sign up to set email alerts
|

Associations between overweight and obesity and health enhancing behaviours among female nurses in Poland

Abstract: Introduction and objective. The nursing profession entails many negative factors and high risk of chronic diseases, including overweight and obesity. The aim of the study is to investigate the prevalence of overweight and obesity and health enhancing behaviours in Polish female nurses, and associations between overweight and 4 groups of such behaviours, age and shift work. Materials and method. The analysis covered data obtained through cross-sectional survey carried out in a group of 994 nurses with an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…In our cohort, nearly half (45.5%) of nurses were overweight or obese, which reflects the percentage of adult women in Poland as a whole (40% in 2017) [ 29 ]. A similar percentage of overweight/obesity (44%) was observed earlier in Polish nurses [ 30 ]. Although this indicator of overweight/obesity is lower than that observed in other countries, including Australia (61%) [ 17 ], Scotland (69%) [ 31 ] and the USA (49%) [ 32 ], it is still worth reducing it.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our cohort, nearly half (45.5%) of nurses were overweight or obese, which reflects the percentage of adult women in Poland as a whole (40% in 2017) [ 29 ]. A similar percentage of overweight/obesity (44%) was observed earlier in Polish nurses [ 30 ]. Although this indicator of overweight/obesity is lower than that observed in other countries, including Australia (61%) [ 17 ], Scotland (69%) [ 31 ] and the USA (49%) [ 32 ], it is still worth reducing it.…”
Section: Discussionsupporting
confidence: 85%
“…The assessment of the nutrition disorders of nurses was performed using the My Eating Habits questionnaire [18]. Younger nurses (<31 years old) demonstrated a greater tendency for habitual overeating, in comparison to nurses older than 30 Moreover, overweight and obese nurses demonstrated a greater tendency toward inappropriate nutrition choices, especially with regards to emotional overeating in comparison to the remaining analysed subjects (p = 0.000, One-way ANOVA; Table 2).…”
Section: Nutrition Habitsmentioning
confidence: 99%
“…Almost half (45.5%) of the nurses in our cohort were overweight or obese, which reflects the proportion observed among adult women in the general Polish population (40% in 2014) (Główny Urząd Statystyczny Departament Badań Demograficznych, 2018). A similar percentage of overweight/obesity (44%) was previously observed in Polish nurses (Woynarowska‐Sołdan et al., 2018). Although this rate of overweight/obesity in Poland is lower than that observed in other countries, including Australia (61%) (Perry et al., 2018), Scotland (69%) (Kyle, Neall, & Atherton, 2016) and the United States (49%) (Chin, Nam, & Lee, 2016), it is still worth reducing.…”
Section: Discussionsupporting
confidence: 85%
“…Their median BMI of 23.9 shows that their weight is within normal weight limits, which confirms their healthy habits. Previous studies conducted among nurses showed them to have similar BMI values such as 25.1 or within the healthy weight range (15,16). These studies report that nurses with a healthy weight engage significantly more in health-enhancing behaviors with the desired frequency.…”
Section: Discussionmentioning
confidence: 83%